Successful desensitization in a patient with hypersensitivity to multiple Insulin preparations - case report - Petricău, Carina; Nedelea, Irena; Deleanu, Diana (Medicine and Pharmacy Reports, 2020)
Hypersensitivity to insulin has decreased substantially in the past three decades, since purified human insulin was introduced to replace heterogeneous porcine and bovine preparations. However, human insulin and its analogs still have immunogenic potential that may prove detrimental for hypersensitive insulin-dependent diabetics. In cases of anaphylactic reactions to insulin, rapid desensitization may be considered as a treatment strategy. We present the first case of successful insulin desensitization in Romania for an uncontrolled diabetic patient with type I hypersensitivity to multiple insulin analogs.